A comprehensive review of Patchouli plant Comparison of microwave-assisted hydro-distillation and hydro-distillation methods - Modather, Rayan Hassan; Nour, Abdurahman Hamid; Rosli, Mohd Yunus; Mohammed, Ghada (Current science publishing, 2024)
Patchouli is a major herb that is widely used in the pharmaceutical and fragrance sectors. It is used in traditional medical practices to treat a variety of ailments, including influenza, headaches, a high fever, gastrointestinal discomfort, vomiting, diarrhea, and insect and snake bites. Within aromatherapy, patchouli oil is used to increase sexual desire and to lower stress, despair, and nervous tension. Patchouli oil is still often extracted using conventional techniques that require a lot of time and solvents. Previous investigations served as the basis for this study, which compared the process of extraction of patchouli oil using the techniques of microwave-assisted hydro-distillation and hydro-distillation. Comparisons were made on the basis of extraction time, power, solvents, and the final yield of oil. From these comparisons, we conclude that microwave-assisted hydro-distillation is a suitable method as a new green technology because it requires a shorter extraction time, a small amount of solvents, a small amount of energy, a high oil yield, a low cost, and is environmentally friendly.